2021
DOI: 10.1111/andr.12970
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and male reproduction: Current research and unknown factors

Abstract: Background The testes are suspected target organs of SARS‐CoV‐2. However, the results of studies on the effect of COVID‐19 on male reproduction are controversial. Objective To summarize current research on the effects of COVID‐19 on male reproduction. Methods A systematic review of English literature was performed using PubMed and Ovid Embase up to 18 August 2020. Research articles on the presence of SARS‐CoV‐2 in semen, the effects of the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
(178 reference statements)
0
6
0
1
Order By: Relevance
“…Furthermore, although more research is needed, preliminary data have shown that vaccination has no effect on sperm parameters (6). Some studies have suggested that the infection itself can have an impact on sperm parameters (19), but data are still lacking regarding the severity and infection status at the time of semen collection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although more research is needed, preliminary data have shown that vaccination has no effect on sperm parameters (6). Some studies have suggested that the infection itself can have an impact on sperm parameters (19), but data are still lacking regarding the severity and infection status at the time of semen collection.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Additionally, the lungs are not unique targets of SARS-CoV -2 and other targets include the heart, liver, kidney and the male reproductive system. [3][4][5][6][7] These studies have suggested that COVID-19 might cause systemic disease.…”
Section: Introductionmentioning
confidence: 99%
“…It can also affect male fertility by being infected locally or through spermatogonia stem cells (27). Although it is not clear how much these viruses are present in semen (28), it is extremely important to assess the presence of COVID-19 RNA in semen samples because even a minor risk is not reasonable in treating healthy couples for infertility reasons (29,30). In this study, COVID-19 RNA did not exist in the collected semen samples.…”
Section: Discussionmentioning
confidence: 68%